Construct validity of symptom checklist-90-revised (SCL-90-R) and general health questionnaire-28 (GHQ-28) in patients with drug addiction and diabetes, and normal population - Ardakani, A.; Seghatoleslam, T.; Habil, H.; Jameei, F.; Rashid, R.; Zahirodin, A.; Motlaq, F.; Masjidi Arani, A. (Tehran University of Medical Sciences, 2016)
Background: Given that validity is the baseline of psychological assessments, there is a need to provide evidence-based data for construct validity of such scales to advance the clinicians for evaluating psychiatric morbidity in psychiatric and psychosomatic setting. Methods: This comparative cross-sectional study aimed to investigate the construct validity of the Malaysian version of the GHQ-28 and the SCL-90-R. The sample comprised 660 individuals including diabetics, drug dependents, and normal population. The research scales were administered to the participants. Convergent and discriminant validity of both scales were investigated by Confirmatory Factor Analysis (CFA) using AMOS. The Pearson correlation coefficient was utilized to obtain the relationship between the two scales. Results: The internal consistency of the GHQ-28 and SCL-90-R were highly acceptable, and confirmatory factor analysis confirmed the convergent validity of both scales. The results of this study revealed that the construct validity of GHQ-28 was acceptable, whereas discriminant validity of SCL-90-R was not adequate. According to Pearson correlation coefficient the relationships between three common subscales of the GHQ-28 and SCL-90-R were significantly positive; somatization (r=0.671, P<0.01), Anxiety (r=0.728, P<0.01), and Depression (r=0.660, P <0.01). Conclusions: This study replicated the construct of the Malaysian version of GHQ-28, yet failed to support the nine-factor structure of the SCL-90-R. Therefore, multidimensionality of the SCL-90-R as clinical purposes is questionable, and it may be a better unitary measure for assessing and screening mental disorders. Further research need to be carried out to prove this finding.